SEJARAH PERKEMBANGAN GERAKAN KESEHATAN MENTAL - Aditiyawarman, Indra (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Mental health, similar to the other scientific knowledge, was developed from the reality or experience of human beingssince pre scientific era. Marx Webeer said that human being entered their historical era when the individual mentality has developedand arranged and all the environment aspects support them, so that they could produce their first cultural product that gave a sign of ahistorical era. This means that without mental health, there would not have been any cultural products and such an era like this wouldbe impossible. Mental health is the key of human's personal and social mobility